Isolation and Identification of Lipopeptide-Producing Bacillus velezensis Strains from Wheat Phyllosphere with Antifungal Activity against the Wheat Pathogen Zymoseptoria tritici - Rémi Platel; Mélodie Sawicki; Qassim Esmaeel; Béatrice Randoux; Pauline Trapet; Mohammed El Guilli; Noureddine Chtaina; Ségolène Arnauld; Alexandre Bricout; Alice Rochex; Natacha Bourdon; Patrice Halama; et al. (Agronomy, 2021)
Septoria tritici blotch, caused by the fungal pathogen Zymoseptoria tritici, is a highly significant disease on wheat crops worldwide. The objective of the present study was to find out new bacterial strains with bio-antimicrobial activity against Z. tritici. Two phyllospheric bacteria (S1 and S6) were isolated from wheat ears and identified as Bacillus velezensis strains according to 16S rRNA Sanger sequencing. Antagonistic assays performed with either living strains or cell-free culture filtrates showed significant in vitro antifungal activities against Z. tritici. For the culture filtrates, the half-maximal inhibitory dilution and the minimal inhibitory dilution were 1.4% and 3.7% for the strain S1, and 7.4% and 15% for the strain S6, respectively. MALDI—ToF analysis revealed that both strains synthesize cyclic lipopeptides but from different families. Interestingly, only strain S1 produces putative bacillomycin D. Such differential lipopeptide production patterns might explain the difference observed between the antifungal activity of the culture filtrates of the two strains. This study allows the identification of new lipopeptide-producing strains of B. velezensis with a high potential of application for the biocontrol of Z. tritici.